Periodicals & irregular serials - The Editors, - (Nordic Archaeological Abstracts - NAA, 1983)
Journals with papers abstracted in this number of NAA are listed here. Addresses to the editor or publisher may be obtained by contacting the editor or the members of the editorial board.